Modeling rock-water interaction of fractured aquifer in itabuna/BA region - Teramoto, Elias Hideo [UNESP]; Gonçalves, Roger Dias [UNESP]; Stradioto, Marcia Regina [UNESP]; Engelbrecht, Bruno Zanon [UNESP]; Chang, Hung Kiang [UNESP] (Universidade Federal do Rio de Janeiro, 2019)
This research aimed to investigate the geochemical mechanisms that govern the strong hydrochemical variations in the fractured aquifers of the Itabuna/BA region. Plagioclase and quartz comprise the major mineralogy of metatonalite/ metatrondhjemite rocks, while plagioclase, pyroxenes and amphiboles comprise the major mineralogy of metabasic rocks. Zeolites, chlorites and montmorillonites comprise the main mineral phases generated by rock/water interaction. Conceptually, three distinct processes act on the hydrochemical variations of the aquifer. The first one is represented by the interaction of meteoric water with marine aerosols, while the second one is governed by high evapotranspiration rates that increase the water salinity, and the third one is represented by the interaction with metatonalite/metatrondhjemite and methasic rocks. The geochemical simulations were able to reproduce the compositional variations observed in the field. The increase of Cl- can be attributed to the interaction of precipitated meteoric water with marine aerosols and subsequent evaporation, whereas the increase of Ca2+, Na+, Mg2+ and HCO3 - is due to the weathering of plagioclase, pyroxenes and amphiboles.
Modelagem da Interação Água/Rocha nos Aquíferos Fraturados da Região de Itabuna/BA
Keywords: Fractured aquifer; Rock/fluid interaction; Silicate weathering